Diagnostic validity of p16, E-cadherin, cyclin D1, p53, and HPV E6/E7 mRNA in CIN 3-like squamous cell carcinoma of the cervix - Xing, Zhao; Danhua, Shen; Xiaobo, Zhang (Frontiers in Oncology, 2024)
Objective Cervical intraepithelial neoplasia grade 3 (CIN 3)-like SCC is a recently identified deceptive growth pattern that closely mimics endocervical crypt involvement by CIN 3. As CIN 3-like SCC is indistinguishable from endocervical crypt involvement by CIN 3, it poses a significant challenge for pathologists. Method We examined 23 cases of CIN 3-like SCC, 6 of which also had concomitant conventional invasive SCC, and 9 cases of endocervical crypt involvement by CIN 3 as a control group. Immunohistochemistry was used to investigate the expression of p16, E-cadherin, cyclin D1, and p53, and the expression of human papillomavirus (HPV) E6/E7 mRNA, the key virus carcinogen of HPV, was detected. The clinicopathological, immunohistochemical, and molecular characteristics of endocervical crypt involvement by CIN 3, CIN 3-like SCC, and the concomitant conventional invasive SCC element were examined. Result CIN 3-like SCC exhibited a characteristic morphology similar to endocervical crypt involvement by CIN 3, with pushing borders invading into the wall of the cervix, often to a significant depth in most cases. Immunophenotypic features of E-cadherin, p16, cyclin D1, and p53 differed between CIN 3-like SCC and conventional invasive SCC, both in staining intensity and region. E6/E7 mRNA expression was higher in CIN 3-like SCC than in endocervical crypt involvement by CIN 3 (P < 0.05). Conclusion CIN 3-like SCC is the type of cancer, presenting numerous challenges and potential for confusion as it mimics the phenotypes of endocervical crypt involvement by CIN 3.